Chapter La prospettiva della lingua giuridica - Bambi, Gianluca (Proceedings e report, 2023)
The norms and uses of gender language are not mere practical rules, but imply a radical (even revolutionary) change in the philosophy of society and of language, and can constitute - if applied in a flexible and reasoned way - a fundamental stimulus for language juridical reaches what should be its essential character, according to the idea of ​​the greatest jurists: clarity.